VELIZIY-ZAKHARCHENKO CIRCLE (CEREBRAL ARTERIAL CIRCLE) AND ITS ROLE IN CEREBRAL BLOOD CIRCULATION, ALONG WITH OBSERVED PATHOLOGIES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The Veliziy-Zakharchenko circle, or the cerebral arterial circle (circulus arteriosus cerebri), is an important anastomotic structure in cerebral blood circulation. It connects the anterior (internal carotid arteries) and posterior (vertebrobasilar system) circulatory systems, providing collateral blood flow. This circle plays a key role in protecting the brain from ischemia. However, its anatomical variants are common and can increase the risk of stroke, aneurysm, and other cerebrovascular diseases. The article details the anatomy of the circle, its physiological role, anatomical variants, observed pathologies, and their clinical significance. Research results show that the complete form of the circle occurs in only 20-50% of cases; in the remaining cases, hypoplasia, aplasia, or fetal-type variants are present, which can lead to circulatory disturbances. The article may provide practical benefits to specialists in neurosurgery, neurology, and radiology.